Política de informação nacional e assimetria de informação no setor de telecomunicações brasileiro - Rodrigo Moreno Marques (2010)
The research sought to establish an interlocution between the themes of national information policy and information asymmetry, focusing on the telecommunications sector in Brazil. The general objective of the investigation was to apprehend how information asymmetry is materialized in the regulatory framework of this sector and the reasons for its occurence in this context. The methodology adopted was based on the legal rationality viewpoint and it was constructed through the triangulation of three complementary analysis: the course of the brazilian telecommunications legislation enactment, the discourse of those who developed this legal apparatus and the content of the sanctioned legislation. The analysis showed that information asymmetry is displayed in the legal framework in a diversified and contradictory way. The comparison between the public and the private regime that rules the telecommunication services demonstrated that the private regime is a locus basically characterized by the information asymmetry. Due to examination of the dialetical interaction between the social actors who took part in the creation of the law, we were able to infer that this legislation is a result of a conflict of interest beetwen the public and the private which take place in the nacional context, with strong international influences. In this arena, the information and telecommunications technologies unveil a field in which mercantile interests have hegemonic domain and the information asymmetry is a powerful tool for maintaining this hegemony. However, the legal rationality viewpoint and its dialectical perspective emphasize, in this context, the coexistence of the thesis and the antithesis, forming a unity of opposites demonstrating that in this structure resides the germ which can transform it.